Coal Seam Gas projects: Proposed policy model for compensation and benefits sharing. (October 2019) - Martin, Nigel; Rice, John
Abstract: Australia had reserves of over 258, 888 petajoules or 6.65 trillion cubic metres of unconventional Coal Seam Gas (CSG) at the end of 2014. The exploration for this rich source of energy requires proponent firms to negotiate access and compensation with landholders under the relevant state policies and regulations. In this study, a summative payment and benefits model is proposed and built using inputs to a dual pass governmental review into compensation for landholders hosting CSG energy projects in New South Wales, Australia. This theoretical model exposed that landholder compensation and production payments policies and regulations are inadequate and require expedited improvements and revisions. Specifically, the potential long term impacts of CSG extraction; landholder injurious affections in relation to personal health, loss of amenity, and diminution of current and future land use; and further consideration of neighbour compensation and compulsory land acquisition options are policy prescriptions that require deeper governmental consideration and analysis. In addition, the replacement of monetary compensation with long term production benefits may offer landholders increased sources of ongoing compensatory income, and thus requires more policy and regulatory exactitude. Graphical abstract: Image 1 Highlights: Highlights 6.65 trillion cubic metres of Coal Seam Gas (CSG) reserves in Australia. Describes a theoretical summative compensation and benefits sharing model. Shows typical rates of landholder compensation of A30, 000–50, 000 per annum. Exposes the lack of compensation mechanisms for long term CSG extraction impacts. Outlines CSG policy and regulations deficiencies and proposed improvements.